Strategic Communication of Indonesian Parliament in Countering Political Disinformation - Dwiki Setya Hendrawan; Priyanto; Fauzia G. Cempaka Timur (Cita konsultindo, 2026)
This research aims to analyze the function of strategic communication in combating political disinformation within The House of Representatives of the Republic of Indonesia. This study seeks to elucidate the necessity for communication tactics to evolve in response to the emergence of digital information environments, characterized by the swift dissemination of disinformation via digital platforms that shape public perception. The research examines digital disinformation and strategic communication, with the use of narrative tactics and the Ends-Ways-Means paradigm in enhancing institutional communication. The findings reveal that disinformation encompasses not only the spread of false information but also the creation of narratives that influence public perception, necessitating institutions to transition from reactive measures to more proactive and systematic communication strategies. Strategic communication significantly influences public perception, affects information interpretation, and upholds institutional credibility, especially through counter-narratives and alternative narratives that address false information. Moreover, effective communication necessitates consistency in messaging, active public interaction, and the capacity to function within dynamic digital settings. This study advances strategic communication strategies inside political institutions, specifically aimed at bolstering public trust, sustaining institutional legitimacy, and improving resilience against digital disinformation in modern political environments.